Tapping into the edible fungi biodiversity of Central India - ALKA KARWA; MAHENDRA K. RAI (Society for Indonesian Biodiversity, 2010)
Karwa A, Rai MK (2010) Tapping into the edible fungi biodiversity of Central India. Biodiversitas 11: 97-101. Melghat forest in Central India was surveyed for occurrence of wild edible fungi and their prevalent favorable ecological factors. Studies were carried out for three consequent years in the months of June to February (2006-2008). A total of 153 species of mushrooms were recorded, collected, photographed and preserved. The enormous biomass in the forest favors variety of edible and medicinal mushrooms. Dominating species belong to genera Agaricus, Pleurotus, Termitomyces, Cantharellus, Ganoderma, Auricularia, Schizophyllum, Morchella, etc. The biotechnological potential of these important mushrooms is needed to be exploited. These studies will open new avenues in improvement of breeding programs of commercially cultivated mushroom species.Key words: biodiversity, mushrooms, Agaricus, Pleurotus, Ganoderma, medicinal